The problems of development of national state - Makštutis, Antanas (Journal of Business Economics and Management, 2007)
The paper analyzes the global economic factors of the development of the national state in the European Union (EU). The place of the national state is shown under globalization in the common EU space where under the conditions of a free market complicated tasks are being formed: development of progress, promotion of democracy in the territory of the state, and activation of the public activity. Problems of the national state and public development as well as ways of their solution are described. Analysis is given of the opportunities for modernization of the organization in the national market and the common EU space, factors related to optimization of human labour are determined and presented, and methods are foreseen for solving the future political, economic and social problems in the EU under the conditions of globalization. First Published Online: 14 Oct 2010